2014
DOI: 10.1371/journal.pone.0091533
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Patterns of Intermediate Uveitis in a Tertiary Institution in Singapore

Abstract: PurposeThe study aims to describe the characteristics and etiologic causes of intermediate uveitis (IU) patients seen by a tertiary eye center in Singapore over 8 years.MethodsThis was a retrospective analysis of the clinical records of consecutive new cases of IU that presented to the uveitis subspecialty clinic from 2004–2011 at Tan Tock Seng Hospital. Data collected included demographics, clinical and laboratory findings. Diagnoses were based on standardized clinical history, ophthalmological examination an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Epidemiologic knowledge is important to guide clinicians in their consideration of differential diagnoses and clinical investigations. [ 7 ] Changing pattern of any disease in a subset of the population is an important health indicator. [ 8 ] There are lots of similar reports from different parts of India and world.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic knowledge is important to guide clinicians in their consideration of differential diagnoses and clinical investigations. [ 7 ] Changing pattern of any disease in a subset of the population is an important health indicator. [ 8 ] There are lots of similar reports from different parts of India and world.…”
Section: Discussionmentioning
confidence: 99%
“…15 All of the patients in our study required treatment, while other studies reported the use of treatment in 75.8-77.5% of their patients. 15,35 In our patients, the most common treatments used were corticosteroids, followed by oral antimetabolites; and the most used adjuvant therapy were topical NSAIDs in cases in which macular edema was present. Similarly, other studies reported systemic corticosteroids to be the most common treatment, followed by oral immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 85%
“… 15 All of the patients in our study required treatment, while other studies reported the use of treatment in 75.8–77.5% of their patients. 15 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Acute or subacute presentation and dense vitritis, especially unilaterally, should suggest a differential that includes necrotizing herpetic retinopathy, toxoplasma chorioretinitis, and endophthalmitis. In one series of intermediate uveitis, patients with tuberculosis had more severe vitritis [19].…”
Section: Infectionmentioning
confidence: 95%
“…Miserocchi et al reviewed 24 uveitis surveys reporting over 26,000 patients that were published before 2012; the average reported prevalence of intermediate uveitis was 9.5 +/À 5.6% [18]. Incident cases of intermediate uveitis accounted for 5.7% of 1168 new cases of uveitis presenting from 2004 to 2011 in Singapore [19].…”
Section: Epidemiology Prevalencementioning
confidence: 99%